The Unity Of Italy And Syme’ s Augustus: Nationalism, Fascism And Elites In The Interwar Period - Wulff Alonso, Fernando (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
Historiographical reflection on Syme and his Roman Revolution has not sufficiently highlighted the importance of his perspective on Italy. Under Augustus, Rome, i.e., the Sullan oligarchy monopolizing public office, would have been defeated by Italy, i.e., the Italian elites, when finally called to participate in the new political system by Augustus. In addition to highlighting the need for historical criticism of such a reductionist and precarious model, this paper also points to the confluence in his thought of inherited nationalist models of collective identities, their mommsenian application to Italy, and imperialist and even Mussolinian perspectives. The continuity of nationalist models also explains the lack of sufficient critical approaches to this central aspect of Syme’s thought